ASPECTUAL OPPOSITION OF VERBS OF VERTICAL MOTION IN RUSSIAN AND UZBEK (International journal of artificial intelligence, 2026)
This research is devoted to a comparative-typological analysis of the aspectual opposition in verbs of vertical motion in Russian and Uzbek. The study examines the grammatical and lexical means of expressing the perfective and imperfective aspects in both languages, focusing on verbs denoting upward and downward movement (e.g., Russian подниматься/подняться, опускаться/опуститься; Uzbek ko‘tarilmoq/ko‘tarmoq, tushmoq/tushirmoq). The work identifies significant structural differences: Russian relies on a binary grammatical system of aspect expressed through prefixation and suffixation, while Uzbek expresses aspectual meanings analytically through auxiliary verbs, adverbials, and context. The findings reveal that the category of aspect in vertical motion verbs is a source of interlingual interference, requiring a functional-semantic approach in teaching and translation.